Fillier. North River. Photograph of people in a livingroom. (1958)
A photograph of 5 people, an older woman, 2 young women, and 2 young men, in a livingroom. Arthur Fillier, Gordon FIllier, Florence (Dawe) Fillier (Back left), Jessie Fillier (back mid), Florence (Flossie) Fillier, August 1958.